2022
DOI: 10.5380/rf.v52i2.82657
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF INITIAL DENSITY ON BIOMASS PRODUCTION IN A Pinus taeda L. PLANTATION IN THE CENTRAL-SOUTH REGION OF PARANÁ, BRAZIL

Abstract: The evaluation of the productive potential of a forest plantation through biomass production is fundamental for managing and planning forest-based industries, with the spacing one of the factors that has influence on biomass production. This study aimed to evaluate the production of aboveground biomass in Pinus taeda L. stands as a function of the spacing, in which three different stands (2.0 m x 2.0 m (smallest), 3.0 m x 2.0 m (medium) and 4.0 m x 2.0 m (larger)), implanted in the municipality of Irati, Paran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results of pine needle yield biomass obtained in this study are comparable to those of other authors. For the plantation of the 15-year-old Pinus taeda stand, 6.06 to 8.60 Mg•ha −1 was obtained, depending on the planting spacing used [28]. In turn, Watzlawick et al [29], also examined Pinus taeda, and showed the following values of needle biomass: for a 14and 16-year-old plantation 5.62 Mg•ha −1 ; for a 19-year-old plantation 3.68 Mg•ha −1 , and for a 21-year-old plantation 8.06 Mg•ha −1 .…”
Section: Pine Needle Biomass Yieldmentioning
confidence: 99%
“…The results of pine needle yield biomass obtained in this study are comparable to those of other authors. For the plantation of the 15-year-old Pinus taeda stand, 6.06 to 8.60 Mg•ha −1 was obtained, depending on the planting spacing used [28]. In turn, Watzlawick et al [29], also examined Pinus taeda, and showed the following values of needle biomass: for a 14and 16-year-old plantation 5.62 Mg•ha −1 ; for a 19-year-old plantation 3.68 Mg•ha −1 , and for a 21-year-old plantation 8.06 Mg•ha −1 .…”
Section: Pine Needle Biomass Yieldmentioning
confidence: 99%